2017
DOI: 10.1098/rsos.161016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen evolution reaction on hybrids of cobalt phosphide and molybdenum phosphide

Abstract: Production of hydrogen from water electrolysis has stimulated the search of sustainable electrocatalysts as possible alternatives. Recently, cobalt phosphide (CoP) and molybdenum phosphide (MoP) received great attention owing to their superior catalytic activity and stability towards the hydrogen evolution reaction (HER) which rivals platinum catalysts. In this study, we synthesize and study a series of catalysts based on hybrids of CoP and MoP with different Co/Mo ratio. The HER activity shows a volcano shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…However, this method currently accounts for ∼4% of the worldwide hydrogen production because of the high cost of noble metal catalysts . Therefore, earth-abundant transition metals and their alloys (Ni, Ni–Fe, Ni–Co, Co–Mo) as well as transition-metal phosphides (TMPs), , nitrides, carbides, and chalcogenides are being investigated as low-cost, earth-abundant electrocatalysts for sustainable hydrogen generation technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method currently accounts for ∼4% of the worldwide hydrogen production because of the high cost of noble metal catalysts . Therefore, earth-abundant transition metals and their alloys (Ni, Ni–Fe, Ni–Co, Co–Mo) as well as transition-metal phosphides (TMPs), , nitrides, carbides, and chalcogenides are being investigated as low-cost, earth-abundant electrocatalysts for sustainable hydrogen generation technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Their elemental makeup is generally denoted as MX 2 , where M is a transition metal and X is a chalcogen, ,, and they have fascinating research interest owing to their abundance and superior HER electrochemical activity . Previous studies have shown that TMDCs have tunable electronic structure which can enhance their intrinsic HER electrochemical properties to provide efficient catalysts. In particular, nanocrystalline TMDC structures are having exposed sulfur or selenide edge sites to catalyze the hydrogen evolution rather than the inert bulk form. , …”
Section: Introductionmentioning
confidence: 99%
“…Both the Co-and Ni-incorporated MoP samples exhibited the highest catalytic activities among the samples reacted for 1.5 hours, sharing the same trends as their geometrical area-normalized polarization curves. Recent studies have reported a volcano-shaped relationship between HER performance and the ratio of metal species in a bimetallic TMP 34,58 ; the excessive addition of dopant metal cations inhibits NP catalytic activity. The extended reaction time did not necessarily improve electrocatalytic activity due to NP agglomeration and compositional changes.…”
Section: Resultsmentioning
confidence: 99%